ANALISIS DAYA DUKUNG TIANG GROUP PADA TANAH BERLENSA DI KOTA BANJARMASIN DENGAN PLAXIS 2D - Yayuk Setiyowati (Jurnal Teknologi Berkelanjutan, 2018)
This research is a small-scale study by making a pile group model in finite element with variable influence of the thickness of the sand lens (sand lens), diameter of pile and pile distance to the pile group capacity. Sand-lined soil layer modelling was analysed using elastic linear modelling contained in the Plaxis program. Soil Data Modelling is taken from the Gatot Subroto Banjarmasin flyover project. Then the pile group modelling is made by modelling the plane lines of the piles simplified as wall elements or called pile plane strains. To equivalent the depth of the actual wall element to the actual conditions in the field where the pile groups are lined up backwards, then the formula equivalent to rigidity is used as described by Andre Rytenius in his dissertation master. In this thesis, the bearing capacity of a single pile foundation is analysed using the Meyerhof and Hanna's methods. The results of the calculation of the pile group capacity of a single pile foundation (40 m) based on manual calculations obtained results of 10438.1477 kN / m2. With Plaxis, the pile group capacity is 9000 kN / m2. The pile group capacity of a single pile in the lens layer of PLAXIS results is smaller than the theoretical the pile group capacity calculation results. The pile group capacity on the lens layer of PLAXIS results obtained for the same diameter incrrasing. A better pile configuration to be applied to sandy soil is a symmetrical 4 pile configuration, where the pile group capacity produced in this configuration is higher than the 9 symmetrical pile configuration.